Clinicopathological features and prognosis of patients with pregnancy‐associated breast cancer: A matched case control study. Issue 4 (2nd March 2021) - Zhang, Ruyan; Liu, Xiaoran; Huang, Wenfa; Shao, Bin; Yan, Ying; Liang, Xu; Ran, Ran; Song, Guohong; Di, Lijun; Jiang, Hanfang; Li, Huiping
Abstract: Aim: We aimed to clarify tumor features and prognosis of pregnancy‐associated breast cancer (PABC) among Chinese women. Methods: PABC was defined as breast cancer diagnosed during pregnancy or within a year after delivery. Patients with PABC were selected from breast cancer cases of women ≤45 years treated at our institution between December 2012 and December 2017, and one non‐PABC control was matched for stage, age, and year of diagnosis for each case. Results: Forty‐one women with PABC were identified (22 diagnosed during pregnancy and 19 within 1 year of delivery). There were significantly more progesterone receptor (PR)‐ and triple‐negative tumors in the PABC (56.1% and 24.4%, respectively) than in the non‐PABC group (31.7% and 4.9%, respectively) ( P = .045 and .026, respectively). Human epidermal growth factor receptor 2 positivity was the same in both groups (31.7%). Median disease‐free survival (DFS) was 29.0 months (95% confidence interval [CI], 6.5‐51.5 months) in the PABC and 40.9 months (95% CI, 22.8‐58.8 months) in the non‐PABC group ( P = .167). Median overall survival (OS) was 82.8 months in the PABC (95% CI, 39.3‐126.5 months) versus 80.1 months (95% CI, 56.7‐103.6 months) in the non‐PABC group ( P = .131). Conclusion: Histological features were similar in both groups, except that PR‐ and triple‐negative tumors were more frequent in the PABC group. Survival analyses show similar OS for patients with PABC and non‐PABC. DFS tended to be shorter in the PABC group; however, this difference was not statistically significant. Abstract : After matching PABC cases with non‐PABC cases for stage and age (±1 year), as well as year of diagnosis secondarily (±1 year), on survival analysis, the median DFS tended to be shorter in women with PABC than in non‐PABC; however, this difference was not statistically significant and the median OS of the two groups were almost the same.